2008
DOI: 10.2166/wst.2008.429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on Fenton process using estimation of hydroxyl radical with salicylic acid as trapping reagent

Abstract: This study estimates the yield of hydroxyl radical using salicylic acid as the trapping reagent and investigates the relationship between hydroxyl radical and pH value. The formation and variation of hydroxyl radical under different pH values were evaluated using reaction products, 2,3-DHBA, 2,5-DHBA, and catechol. The formation rate of hydroxyl radical was dependent on the ratio of ferrous ion to hydrogen peroxide and pH values. The difference between various pH values was explored. The kinetics and mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 19 publications
2
33
0
1
Order By: Relevance
“…2,5-DHBA and 2,3-DHBA were suggested previously to be synthesized by a nonenzymatic reaction in which SA scavenged hydroxyl radicals (Maskos et al, 1990;Chang et al, 2008). The glycosides of 2,5-DHBA and 2,3-DHBA were distributed abundantly in Arabidopsis and were suggested to be formed predominantly from the substrate SA via the IC pathway (Bartsch et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…2,5-DHBA and 2,3-DHBA were suggested previously to be synthesized by a nonenzymatic reaction in which SA scavenged hydroxyl radicals (Maskos et al, 1990;Chang et al, 2008). The glycosides of 2,5-DHBA and 2,3-DHBA were distributed abundantly in Arabidopsis and were suggested to be formed predominantly from the substrate SA via the IC pathway (Bartsch et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SA can scavenge hydroxyl radicals (•OH), resulting in the non-enzymatic formation of both 2,3-and 2,5-DHBA in vitro, with the ratio of these products dependent upon iron ion concentrations and pH (Maskos et al, 1990;Chang et al, 2008). Although highly localized, non-enzymatic production of these compounds could occur during the activation of defences, Bartsch et al (2010) argue that they are predominantly formed enzymatically as i) the levels of total (free plus sugar conjugated) 2,3-DHBA and 2,5-DHBA were not necessarily comparable in Arabidopsis of different ages or mutant backgrounds, and ii) mutations in the Arabidopsis rboh genes, which impact pathogeninducible ROS generation and therefore would be expected to alter non-enzymatic 2,3-and 2,5-DHBA formation, did not affect total 2,3-DHBA accumulation (2,5-DHBA was not analyzed).…”
Section: Conversion To Dihydroxybenzoatesmentioning
confidence: 99%
“…Previous studies have shown that an acidic pH level near 3 is usually optimum for Fenton’s oxidation processes (Zepp 1992; Ndjou’ou and Cassidy 2006; Papadopoulos et al. 2007; Chang et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that an acidic pH level near 3 is usually optimum for Fenton's oxidation processes (Zepp 1992;Ndjou'ou and Cassidy 2006;Papadopoulos et al 2007;Chang et al 2008). The main features of the Fenton system are said to be based on reagent conditions, thus, [Fe 2+ ], [Fe 3+ ], [H 2 O 2 ] and the reaction characteristics (pH, temperature and the amount of organic and inorganic constituents) (Yoon et al 2001).…”
Section: Introductionmentioning
confidence: 99%